Selection of Prospective Drought-Tolerant Cocoa Hybrids Based on Additive Main Effect and Multiplicative Interaction Analyses - Bayu Setyawan; Agung Wahyu Susilo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Global warming impact in increasing temperature and becomes threat for cocoa production because growth of cocoa depends on the amount of water available in the environment. The objective of this study was to describe cocoa hybrid that may potentially be developed as drought-resistant cocoa hybrid. The study used 14 types of cocoa hybrids and ICCRI 06H as control. Those plants were approximately 4 years old and the hybrids were planted in Sumber Asin Experimental Station and Kendeng Lembu Plantation. The variables being observed to evaluate 2015 El-Nino effect were percentage of growing plants, tree diameter, jorquette height, flush and flower intensity in 2016. Analysis of variance, correlation and additive main effect and multiplicative interaction (AMMI) biplot were used to find out which hybrids were potentially drought-resistant. The finding showed that there was significant interaction between the genotypes (hybrids) and environment towards the percentage of growing plants, tree diameter, flush and flower intensity. The correlation between the variables showed that there was significant, negative correlation between the percentage of growing plants and height; even though there was significant correlation between the two, it was quite low. There was significant correlation between the tree diameter and the jourquette height while there was not any between the tree diameter and the percentage of growing plants. The AMMI analysis classified the drought tolerant hybrids into two groups, (1) cocoa hybrids adaptive to both normal as well as the temperature and water scarcity (drought), was ICCRI 03 x KW 617, and (2) drought tolerance cocoa hybrids, was KW 516 x KW 617.